REASON AND THINKING: THE IMPORTANCE OF INTELLECTUAL GAMES IN SCIENTIFIC CREATIVITY - Shoira Kubaeva (Western European Studies, 2024)
the article highlights the importance of intellectual games in the development of human consciousness, thinking and scientific thinking. It is shown that games, especially intellectual games, play an important role in self-expression and strengthening of knowledge. The influence of games such as chess, puzzles, strategic games on scientific thinking, logical and abstract thinking is analyzed. The article also considers the role of intellectual games in socio-cultural development, in particular, as a pedagogical tool in educational practice. It is emphasized that creative and communicative abilities of a person can be developed through intellectual games.
Keywords: intellectual games; scientific thinking; cognitive ability